2021
DOI: 10.1161/circresaha.120.317933
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting Mitochondria-Inflammation Circuit by β-Hydroxybutyrate Mitigates HFpEF

Abstract: Rationale: Over 50% of heart failure patients have preserved, rather than reduced ejection fraction (HFpEF vs. HFrEF). Complexity of its pathophysiology and the lack of animal models hamper the development of effective therapy for HFpEF. Objective: This study was designed to investigate the metabolic mechanisms of HFpEF and test therapeutic interventions using a novel animal model.Methods and Results: By combining the age, long-term high-fat diet and desoxycorticosterone pivalate challenge in a mouse model we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
207
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 253 publications
(235 citation statements)
references
References 40 publications
10
207
4
Order By: Relevance
“…First, the current data did not address the exact mechanism whereby O-GlcNAcylation activates G6PDH. In our opinion, it could be due to direct activation via O-GlcNAc modification of serine/threonine residues in G6PDH catalytic domain, similar to a recent report about β-OHB-mediated activation of citrate synthase [ 51 ], or indirect regulation such as competitive inhibition of other post-translational modification machinery on G6PDH. More detailed studies, like site-specific mutagenesis, are required to test these possibilities.…”
Section: Discussionsupporting
confidence: 84%
“…First, the current data did not address the exact mechanism whereby O-GlcNAcylation activates G6PDH. In our opinion, it could be due to direct activation via O-GlcNAc modification of serine/threonine residues in G6PDH catalytic domain, similar to a recent report about β-OHB-mediated activation of citrate synthase [ 51 ], or indirect regulation such as competitive inhibition of other post-translational modification machinery on G6PDH. More detailed studies, like site-specific mutagenesis, are required to test these possibilities.…”
Section: Discussionsupporting
confidence: 84%
“…Although β-OHB is an energy substrate, there was no change in ATP production in response to β-OHB treatment (Figure 6e). In contrast to the increased ketone utilization previously reported in end-stage heart failure [22] and HFpEF (heart failure with preserved ejection fraction) [23], the β-OHB treatment did not contribute to cardiomyocyte ATP production under hypoxic conditions, suggesting that the cardiomyocytes did not use ketone bodies as an alternative energy source.…”
Section: β-Ohb Metabolisms Were Obscured Under Hypoxic Conditions In Cardiac Myocytescontrasting
confidence: 87%
“…This observation is obscure because it is contradictory to the alterative ketone utilization observed in advanced-stage heart failure. Previous research has shown that hypertrophied and failing hearts undergo regulatory gene reprogramming to increase the uptake and oxidation of ketone bodies [23,28]. Specifically, the expression of BDH1 and the transporter SLC16A1…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on HFpEF supported that systemic inflammation may be the association between comorbidity and HF ( 191 ). The IL-1β and IL-18 signaling pathways may be novel drug targets for HFpEF, which are important in the mitochondria-inflammation circuit ( 192 ).…”
Section: Link Between Heart Failure and Comorbiditiesmentioning
confidence: 99%